Level of knowledge on disaster management for children and attitude towards disasters of pediatricians from the Pediatric Intensive Care Unit of the Centro Médico Naval – Callao, 2018–2019 - Palomino , Carlos A. (2021)
Objective: To determine the correlation between the level of knowledge on disaster management for children and the attitude towards disasters of pediatricians from the Pediatric Intensive Care Unit of the Centro Médico Naval – Callao from December 2018 to February 2019. Materials and methods: The level of knowledge was established using a questionnaire based on a course on disaster management from the American Academy of Pediatrics. The attitude towards disasters was determined using a validated self-administered Likert-scale questionnaire that measured the cognitive, behavioral and affective areas. The IBM SPSS Statistics V25 was used for the statistical analysis. Frequencies and percentages were employed for the descriptive statistics. The Spearman’s correlation coefficient with a significance level of p < 0.05 was used for the inferential statistics. Results: Eighty percent (80 %) of the study population had a moderate level of knowledge and 76 % had an indifferent attitude. A moderate positive correlation level (0.505) with a significance level of p < 0.05 was found. Conclusions: A correlation between the level of knowledge and the attitude towards disasters was demonstrated. Therefore, it is necessary to train the emergency personnel, particularly the pediatricians.